Một phương pháp cấu trúc mạng ngữ nghĩa - Thanh, Le Tu (Journal of Computer Science and Cybernetics, 2018)
This paper deals with the construction of Semantic Networks, one of the  knowledge representation languages. The definitions of the Basic Networks, of the Related Set of Basic Networks are introduced to decompose and  construct any Semantic Networks. There are the algorithms DEC and CONS to do these works, and  some operations on Networks may be expressed with them. The Boundary Set of an  internal node is introduced, which  shows the relationship between nodes on a graph representing Semantic Network. In last chapter, the concept  of installed Basic Networks is considered based on the list definitions.